Immune correlates of NF-κB and TNFα promoter DNA methylation in Japanese flounder (Paralichthys olivaceus) muscle and immune parameters change response to vibrio anguillarum infection. Issue 119 (December 2021) - Yang, Jun; Liu, Binghua; Li, Xiaohui; Li, Guangling; Wen, Haishen; Qi, Xin; Li, Yun; He, Feng
Abstracts: Vibrio anguillarum infection can activate NF-κB/TNFα pathway in the immune organs of fish. Fish muscle is also an important immune organ, but the research on its immune function is few. Our aim was to study regulating mechanism of NF-κB and TNFα gene expressions in the muscle of Japanese flounder ( Paralichthys olivaceus ) which was under Vibrio anguillarum infection (0, 24, 48, 72 and 96 h). The results showed that the expressions of NF-κB and TNFα increased significantly at 48 h, and there was a significant positive correlation between them. In situ hybridization confirmed the co-existence of NF-κB and TNFα genes in Japanese flounder muscle. Interestingly, the expression of the TNFα gene was regulated by the DNA methylation and its methylation level was negatively correlated with the expression. The lowest methylation level of TNFα occurred at 48 h under Vibrio anguillarum infection ( P  < 0.05). And more, when the fragment (−2122 ∼ −730) was deleted on TNFα gene promoter, double luciferase activity was the highest, indicating that fragment (−730–0) was the transcription factor binding region. The site (−78 ~ −69) on the fragment (−730–0) binding NF-κB was mutated, and double luciferase activity decreased significantly. The results confirmed that the site (−78 ~ −69) was indeed an important binding site for NF-κB. In addition, the activity of TNFα in the serum of Japanese flounder changed with the prolongation of vibrio anguillarum infection, and the concentration of other immune factors such as ALP, ALT, AST and LDH also changed in the muscle under vibrio anguillarum infection. They all showed a trend of first increasing and then decreasing. Above studies implied that Japanese flounder responded to Vibrio anguillarum infection at the immune level with the change of its methylation status and the activation of transcription factor. By studying the mechanism of immune pathways, understanding the response to immune stress is great significant to the research of fish breeding for disease resistance. Highlights: Immune stress of NF-κB/TNFα pathway immune gene caused by Vibrio anguillarum infection. The change of epigenetic DNA methylation modification caused by Vibrio anguillarum infection. The binding site of transcription factor NF-κB on TNFα promoter region was identified. DNA methylation regulation and transcription factor worked together on immune regulation.